2017
DOI: 10.1016/j.fuel.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Butanol-gasoline blend and exhaust gas recirculation, impact on GDI engine emissions

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Of four isomers, t-butanol was found as the most effective to reduce particle formation. Furthermore, Hergueta et al [174] investigated 33% of butanol containing 5% of ethanol (B33) in a gasoline engine. It was found that the gaseous and particle emissions were successfully decreased with primary particle diameter being unaffected.…”
Section: Particulate Matter (Pm) Emissionmentioning
confidence: 99%
“…Of four isomers, t-butanol was found as the most effective to reduce particle formation. Furthermore, Hergueta et al [174] investigated 33% of butanol containing 5% of ethanol (B33) in a gasoline engine. It was found that the gaseous and particle emissions were successfully decreased with primary particle diameter being unaffected.…”
Section: Particulate Matter (Pm) Emissionmentioning
confidence: 99%
“…Vojtisek-Lom et al [59] determined PM emission reductions for a n-Butanol blending rate of 25% especially for urban and rural driving conditions, while the decrease of PN emission also happens for the motorway part. Hergueta et al [60] concluded that the oxygen content of butanol can decrease the soot formation rate as well as optimize the oxidation rates of the already formed particles. This is especially shown for blending rates up to 33%, reaching PM/PN emission reductions of >50%; however, Vojtisek-Lom et al [61] obtained approx.…”
Section: Resultsmentioning
confidence: 99%
“…Deviation of gaseous and particulate pollutant emissions from butanol-gasoline blend combustion from those of neat gasoline fuel combustion depending on the butanol blending rate. Data derived from: Wigg et al, 2011 refers to [46], Li et al, 2017 refers to [47], Nithyanandan et al, 2016 refers to [48], Dernotte et al, 2010 refers to [50], He et al, 2013 refers to [55], Liu et al, 2019 refers to [58], Vojtisek-Lom et al, 2015 refers to [59], Hergueta et al, 2017 refers to[60], and Vojtisek-Lom et al, 2013 refers to[61].…”
mentioning
confidence: 99%
“…When the intake port injected ethanol is gradually switched to direct injected gasoline, the APN of particles gradually rises. The formation of aggregated particles is strongly related to polycyclic aromatic hydrocarbons in gasoline; and the injection of large amount of gasoline into the cylinder can result in a locally fuel rich zone near the spark plug [34], so the atomization mixing effect is poor and the incomplete combustion can produce large amount of particles. Meanwhile, the reduction of ethanol will reduce the oxygen content in the fuel, which can also contribute to the increase of the particle emissions.…”
Section: Resultsmentioning
confidence: 99%